ANALISIS BAHAYA BENCANA GEMPABUMI DI WILAYAH BITUNG MENGGUNAKAN METODE PROBABILITY SEISMIC HAZARD ANALYSIS - Pamela Sifra Lumingas; Heinrich Taunaumang; Farly Tumimomor; Muhammad Zulkifli (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
Bitung district was an active seismic area in North Sulawesi Province. This is because of platetectonic activity, among other things, subduction of West Molucca Sea and subduction of NorthSulawesi Trench that can cause earthquake disaster. Earthquake is an unpredictable disaster thatcan pose a danger to a region. So the purpose of the research is to minimize the impact of theearthquake disaster. The study conducted with study of the earthquake hazard analytics usingprobability approaches with 500-year-old return period, probability exceeded 10% in 50 years ofbuilding age in condition T= 0 second, T= 0.2 second and T= 0.1 second. PSHA’s calculation in theBitung region were obtained at PGA value of the same amount 1.4g – 1.8g, SA value T= 0.2 secondis 1,7g-2,1g and SA value T= 1,0 second is 0,5-0,6g. as for the turbulence of the result of teconversion of the PGA value being on the VIII-IX MMI scale which means it can cause a seriousrisk of damage to the building.